Sustainable modular biofiltration system with rainshower technology for AQI reform - Vivek Jaiswal; Shubham Singh; Arpit Mangal; Pushpendra P. Singh (Scientific Reports)
Abstract India is the tenth most polluted nation in the world, according to the World Health Organization (WHO) 2022 assessment. Approximately 1.67 million deaths are caused by lung, cardiovascular, stroke, and chronic pulmonary obstruction worldwide (WHO 2024). In 2019, 1.36% of GDP was reported to be lost because of air pollution and related issues. The results presented in this article demonstrate the efficacy of UBREATHE RAIN. Ambient (outside), untested enclosure (reception), and tested enclosure (breathing lounge with 3 Ubreathe Rain) were the 3 test venues that were found based on proximity and interaction to the stubble burning site. The Air Quality Index (AQI) was recorded as the highest sub-index of pollutants involved (CO, PM, SO2, NO2, and O3) through grab sampling. Throughout the studies, the AQI in the tested enclosure was ~ 35% lower than that in the ambient environment and ~ 30% lower in the untested enclosure. Statistical analysis also supported this finding, as the p-value remains < 5% throughout (p-value ≈ 2%). Additionally, temperature and relative humidity changes were examined and demonstrated to represent significantly less of a challenge to the effectiveness of the proposed technology. The experiment’s duration and demographics may have limited the given results and their importance.